Impact of anemia on platelet production and function in acute coronary syndrome: results of long-term single-center registry. (26th April 2021) - Malinova, L; Dolotovskaya, P; Furman, N; Radzhabov, KH
Abstract: Funding Acknowledgements: Type of funding sources: None. Anemia is the most common clinical condition known to increase both ischemic and hemorrhagic risks in patients with acute coronary syndrome (ACS). Despite it"s high frequency there are certain gaps in evidence on how to choose appropriate antiplatelet regimen in anemia, for anemia was among exclusion criteria in almost all randomized clinical trials on efficacy and safety of antiplatelet agents. Purpose of the study: to evaluate prevalence of anemia and it"s impact on platelet production and function in patients admitted to ICU with ACS. Methods. To determine the prevalence and characteristics of anemia we analyzed data from the local single-center long-term registry of coronary heart disease (n total= 4776, n ACS = 765). To evaluate platelet production and function we used data obtained from those patients with ACS in whom platelet function, immature platelet fraction (IPF), thrombopoietin (TPO), stromal cell-derived factor 1 (SDF1), TPO receptors (MPL) and platelet derived microparticles (PDMP) were measured serially at admission, on the second and on the 7th day since ACS manifestation (n = 321). Results. Anemia on admission was verified in 12.5% of ACS, and there were no significant differences in antiplatelet therapy at first medical contact and on admission. Anemia in patients with ACS was accompanied with decreased platelet count, therefore TPO level at admission was higher: 336.23 (141.35; 429.85) ng/mL vs 266.04 (199.16; 341.20) pg/mL, p = 0.050. PDMP level at admission was minimal in anemic patients: 6.75 (5.31; 7.81) vs 26.45 (16.05; 39.35) ng/mL (p = 0.027). There were no significant differences in TPO levels measured on the 2nd and the 7th days, as well as SDF and MPL. IPF was also comparable in anemic patients and those with normal Hb levels. Despite similar platelet function on admission in patients with anemia there was significant increase in platelet ADP-induced aggregation and secretion with maximal level at the 7th day since ACS manifestation: 2 (1; 4) vs 0 (0; 1) Ohm, p = 0.02. Anemia in ACS was characterized with unfavorable myocardial stress and injury biomarkers dynamics: BNP at the 7th day – 1155 (867; 2251) vs 73.4 (40.3; 148.5) pg/mL, and with increase in risk of early adverse (ischemic, but not hemorrhagic) events OR 8.6 CI 1.1; 19.4, p = 0.038. Conclusion. Anemia is a common comorbidity in acute coronary syndrome increasing risk of early complications. Anemia on admission in ACS is characterized by increase of platelet aggregation and secretion despite antiplatelet therapy, and this activation does not result from possible associated changes in platelet production and turnover. Received results underline the risk of early discontinuation of antiplatelet therapy in ACS with anemia, and possible benefits of platelet function monitoring in these patients.